Association between disordered eating and clinical outcomes following a surgical or endoscopic bariatric procedure: A real‐world exploratory study - Georgia Spry; Ashleigh McIntosh; Nicola Gadd; Zoe Martin; Brianna Fear‐Keen; Jennifer Hoult; Isabella R. Maimone; Patrice Jones; Jaimon T Kelly; Skye Marshall (Wiley, 2023)
Abstract Problem Disordered eating, such as binge, graze, and emotional eating, has been strongly linked to weight gain. Improved understanding of disordered eating by adults who elect bariatric weight loss procedures in a real‐world setting is required. Purpose To determine the association between the number and type of disordered eating patterns (DEPs), as described by healthcare professionals during routine care without standardized assessment, with clinical outcomes in adults who elected a bariatric weight loss procedure. Method An observational cohort study recruited laparoscopic sleeve gastrectomy (LSG) and endoscopic sleeve gastroplasty (ESG) patients. DEPs documented in the medical record during routine care were observed and tested for association with events (symptoms, side‐effects, or adverse events), micronutrient deficiencies, weight loss, and attrition. Data were observed up to 12‐month post‐procedure. Results 215 LSG and 32 ESG patients were recruited. The mean number of DEPs was 6.4 (SD: 2.1) and 6.4 (SD: 2.1) in the LSG and ESG cohorts, respectively. Night eating was associated with a higher number of events (p < 0.008) in the LSG cohort, and non‐hungry eating was associated with a higher number of events in the ESG cohort (p < 0.001). ESG patients who had a surgical or medical event by 6‐months post‐procedure had mean 1.78 (95%CI: 0.67, 2.89) more DEPs (p = 0.004). DEPs were not associated with weight loss, micronutrient deficiencies, nor attrition. Conclusion The treating healthcare team believed the LSG and ESG patients experienced a wide variety and high frequency of DEPs requiring multidisciplinary support. Non‐hungry eating and night eating were associated with poorer outcomes following an LSG or ESG. Trial registration The study was prospectively registered with the Australian New Zealand Clinical Trials Registry (ACTRN12622000332729).